2012
DOI: 10.1088/0268-1242/27/3/035019
|View full text |Cite
|
Sign up to set email alerts
|

A TCAD-based modeling of GaN/InGaN/Si solar cells

Abstract: Theoretical efficiency potential of GaN/InGaN/cSi tandem solar cells is investigated using two-dimensional numerical computer simulation (i.e. technology-based computer aided design tool: TCAD). With double-junction GaN/InGaN/cSi tandem design, a conversion efficiency of 27% is achieved using a 1.0 μm In 0.5 Ga 0.5 N absorber of top cell over crystalline silicon (cSi) bottom cell. This efficiency is further improved to 29.0% with grading of the In x Ga 1−x N absorber layer close to the top heterointerface (p +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…Although the different results presented in I-V curves, it was possible to observe similar behavior within each group; in both, as the thickness of the intrinsic layer was increased, the voltage was decreased and current density increased, which coincides with some previously works reported for photovoltaic devices based on GaN [14]. However, although the increase in current density peaked around 32 mA/cm 2 for both groups, a marked difference was observed in the increase of current density for heterostructures with i-GaAs layer thicknesses lower than 400 nm for the reduced thickness of p-GaAs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although the different results presented in I-V curves, it was possible to observe similar behavior within each group; in both, as the thickness of the intrinsic layer was increased, the voltage was decreased and current density increased, which coincides with some previously works reported for photovoltaic devices based on GaN [14]. However, although the increase in current density peaked around 32 mA/cm 2 for both groups, a marked difference was observed in the increase of current density for heterostructures with i-GaAs layer thicknesses lower than 400 nm for the reduced thickness of p-GaAs.…”
Section: Discussionsupporting
confidence: 89%
“…The results obtained in this theoretical study show that to locate the space charge within the intrinsic region, it is required a thickness between 1 and 1.5 microns for i-GaAs, which allows to assume that the intrinsic layer thickness must be at most the order of the absorption length, about 1.2 microns according to what was reported by Nawaz & Ahmad [14]; also, it was observed that increasing excessively the thickness of i-GaAs layer negatively impacts V oc , because the intensity of the internal electric field is reduced and there is an increase in possibilities of recombination of carriers. Therefore, this allows justify why for thicknesses greater than the intrinsic layer, the efficiency peaks that could be attributed to absorption maximum and photogeneration, which subsequently decreases when after that peak only increases recombination and it impacts negatively in device performance.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The photon energy-dependent optical constantsrefractive index, n(E), and extinction coefficient, k(E), of In y Ga 1Ày N material shown below are prerequisite for In y Ga 1Ày N/GaN solar cell modeling [21,22],…”
mentioning
confidence: 99%